Evolution of human cytomegalovirus-seronegative donor/-seropositive recipient high-risk combination frequency in allogeneic hematopoietic stem cell transplantations at Institute of Hematology and Blood Transfusion during 1995-2014 - Němečková, Šárka; Šroller, Vojtěch; Marková, Markéta (Transplant infectious disease, 2016)
BACKGROUND: Human cytomegalovirus (HCMV) establishes lifelong latent infection that can result in severe life-threatening disease in immunosuppressed patients after hematopoietic stem cell transplantation (HSCT). An HCMV-seropositive transplant recipient who receives a graft from a seronegative donor (R+/D-) is at high risk of recurrent HCMV reactivation. METHODS: To assess the incidence of R+/D- combination, we retrospectively evaluated HCMV-seronegative donors for 746 allogeneic HSCT treatments carried out at our center during 1995-2014. In our cohort, 20% HCMV-seronegative HSCT recipients, 21% HCMV-seronegative related graft donors, and 52% HCMV-seronegative unrelated graft donors were included. RESULTS: Analyses of the HCMV serostatus of hematopoietic stem cell donors during 2 consecutive calendar periods (1995-2005 and 2006-2014) showed a significant increase in the proportion of seronegative donors (odds ratio [OR] = 1.947). In addition, the number of HSCT treatments using an unrelated donor increased (OR = 2.376). Finally, the use of grafts from countries with a very low HCMV prevalence increased. CONCLUSION: This increase in HCMV seronegativity in unrelated donors and the increased proportion of unrelated donors were responsible for the increased occurrence of the high-risk combination R+/D- (OR = 1.680). If the reduction in the rate of HCMV-seropositive graft donors continues, an increased frequency of HCMV reactivation events in our transplant recipients can be expected, because of the increasing occurrence of the high-risk R+/D- combination.
Keywords: Cytomegalovirus Infections; transplantace hematopoetických kmenových buněk; Tissue Donors; Virus Activation; Czech Republic; cytomegalovirové infekce; lidé; Cytomegalovirus; dárci tkání; imunokompromitovaný pacient; retrospektivní studie; Humans; Retrospective Studies; Česká republika; aktivace viru; Immunocompromised Host; Hematopoietic Stem Cell Transplantation